Some methods of estimating the spatial pattern point data with application ( comparative study) - Jaufar Mousa Mohammed (Tikrit Journal of Pure Science, 2023)
The idea of this paper is to estimate spatial data points pattern by Inverse distance weighting, Teard surface analysis of first order and Ordinary kriging method, we calculate the mean absolute error MAE and root mean square error RMSE of these methods as standard to determine the best method to be adopted in the forecasting process, we have been using real data in this paper in the field of salinity dissolved in water wells in the province of kirkuk government , which has been obtained from the groundwater body in the Ministry of water Resources 2014 , and that all the calculations have been processed using matlab program with respect to another to methods